2008
DOI: 10.1177/0093854808314368
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Offending, Victim Gender, and Extent of Victim Relationship in Catholic Church Sexual Abusers

Abstract: Despite wide reports of sexual abuse in the Catholic Church, empirical data on Catholic Church sexual abuse have not been readily available. The present study examines factors associated with sex-offender risk assessment along three criteria (repeat offending, victim gender, and victim relationship) on a sample of sexual abusers in the Catholic Church. Data from 4,392 priests with documented allegations of child sexual abuse were used. Logistic regression analysis resulted in significant predictive models for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…For example, clergy abusers are older and a personal history of sexual abuse seems to be a strong predictive factor for recidivism, unlike the general sexual recidivism literature (Hanson & Morton-Bourgon, 2005; Piquero et al, 2008). Being a victim of sexual abuse as a child might, therefore, contribute to the relationship with children and also to the decision to become a priest (Perillo et al, 2008). This hypothesis is supported by a case-control study that compared offending clergy to nonoffending clergy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, clergy abusers are older and a personal history of sexual abuse seems to be a strong predictive factor for recidivism, unlike the general sexual recidivism literature (Hanson & Morton-Bourgon, 2005; Piquero et al, 2008). Being a victim of sexual abuse as a child might, therefore, contribute to the relationship with children and also to the decision to become a priest (Perillo et al, 2008). This hypothesis is supported by a case-control study that compared offending clergy to nonoffending clergy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Strategies of denial and cover-up emerged from institutional cultures which valued secrecy, clerical elitism and the protection of the 'good name' of the Catholic Church and its clerics (McLoone-Richards 2012; Perillo et al 2008;Pilgrim 2012;Wirenius 2011).…”
Section: Institutional Abuse Internationallymentioning
confidence: 99%
“…Nevertheless, a literature base has gradually taken shape, and Perillo et al (2008) have noted similar risk factors that are relevant to both clerical and non-clerical abusers. Haywood et al (1996) reported that clerics convicted of sexual offending tend to be older, better educated, and single when compared to other sex offenders.…”
Section: Reasons For Referralmentioning
confidence: 99%